Climate change trends in some of the rubber growing regions of North-East India - Raj, Shammi (Journal of Plantation Crops, 2015)
Climate change analysis has been conducted using daily surface meteorological datasets in respect of nine parameters from five rubber growing locations in the East and North-East India. Monthly, seasonal and annual variability in meteorological parameters showed decreasing trends in relative humidity, sunshine hours and pan evaporation rates coupled with increasing temperature extremes. Rise in mean temperature was seen to be highest (0.34 0C per decade) for Dhenkanal which experiences dry sub-humid type of climate. The data on relative humidity and temperature also revealed the fact that warm surface temperatures, along with limited moisture availability, may lead to lower relative humidity in the future, since all the stations are away from the moist coastal belts. Decreasing trends in sunshine hours were mainly observed during winter and post monsoon seasons with decreasing number of days even with the optimum required daily sunshine hours. The fact that there were no significant changes in the amount of rainfall or the number of rainy days was in conformity with several earlier reports in the northeast. Mean monthly decadal variations have also been tested with earlier and recent sets. With long term trends in most of the weather parameters, being lesser when compared to that of the traditional rubber growing regions in India, it is imperative that for rubber cultivation to thrive in this non-traditional belt, future policy inputs will have to be based depending on the magnitude of climate change effects.